Degrammaticalization - Norde, Muriel, 1968- (Oxford linguistics., 2009)
Muriel Norde shows that linguistic change via the process of grammaticalization is reversible, and that degrammaticalization can occur on all levels: semantic, morphological, syntactic, and phonological.